Chitinase 3-like protein 1 deficiency ameliorates drug-induced acute liver injury by inhibition of neutrophil recruitment through lipocalin-2 - Kim, Ji Hye; Yeo, In Jun; Son, Dong Ju; Han, Sang Bae; Yoon, Do Young; Lee, Dong Hun; Hong, Jin Tae (Frontiers in Pharmacology, 2025)
Chitinase-3-like protein 1 (Chi3l1) is a member of the mammalian Chitinase-like protein family, and several studies reported that Chi3l1 is associated with various inflammatory diseases as well as liver diseases. Acetaminophen (APAP) is usually used for antipyretic drug, but its overdose induces acute liver injury (ALI). Several studies reported that subsequent inflammatory responses of the immune system play a critical role in the severity and outcome of APAP-induced ALI. In the present study, we investigated the role of Chi3l1 and its mechanism during APAP-induced ALI using Chi3l1 knock-out (KO) mice. We explored the function of Chi3l1 using APAP-injected KO mice and sought proteins associated with Chi3l1 through biological research data program for investigating mechanism. Liver histological analysis revealed that APAP-induced ALI was attenuated in KO mice compared to wild-type (WT) mice. We observed that APAP-induced neutrophil infiltration was decreased in the liver of KO mice compared to WT mice. To investigate this mechanism, we sought proteins potentially associated with Chi3l1 by mRNA sequencing and protein correlation analysis data. We found lipocalin-2 (Lcn2) and examined Chi3l1, Lcn2, and their relationship in the APAP-induced ALI model using recombinant proteins and antibodies. Our results suggest that Chi3l1 deficiency ameliorates APAP-induced liver injury through abrogating Lcn2-mediated neutrophil infiltration in the liver.